Treatment of Ruptured Giant Omphalocele and Gastroschisis with Liver Herniation using a Wound Retractor as a Novel Approach - Nelson, Jana; Wachowiak, Robin; Siekmeyer, Manuela; Knuepfer, Matthias; Thome, Ulrich; Holger, Stepan; Lacher, Martin (European Journal of Pediatric Surgery Reports, 2020)
Ruptured giant omphaloceles (GO) and gastroschisis with total liver herniation are rare cases of exceptionally large abdominal wall defects. Many of these children have lethal outcome. The surgical and postsurgical management are complex. We report on two cases treated with staged surgical repair using a wound retractor as a silo. With this technique, the liver and intestines could be reduced into the abdomen with secondary closure of the abdominal cavity within the first 1 to 2 weeks of life.
Keywords: ruptured giant omphalocele; giant gastroschisis; liver herniation; abdominal wall defects; staged surgical repair